2016
DOI: 10.1111/rda.12675
|View full text |Cite
|
Sign up to set email alerts
|

Cryopreservation of Dog Semen in a Tris Extender with 1% or 2% Soya Bean Lecithin as a Replacement of Egg Yolk

Abstract: Egg yolk is usually included in extenders used for preservation of dog semen. Lecithin is an interesting animal-protein free alternative to egg yolk for semen preservation. The aim of our study was to evaluate soya bean lecithin for cryopreservation of dog semen. Five ejaculate replicates were divided in three equal parts, centrifuged and each pellet diluted with one of the three Tris-based extenders containing 20% egg yolk, 1% soya bean lecithin or 2% soya bean lecithin. Extended semen was loaded in 0.5-ml st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
18
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 28 publications
4
18
0
3
Order By: Relevance
“…The obtained results clearly demonstrated that egg yolk is superior to soybean lecithin in Tris‐citric‐fructose or Tris‐citric‐fructose‐mineral salts extender when considering motility, plasma membrane integrity, acrosome membrane integrity and mitochondrial membrane potential parameters during 10 days of chilling storage. The results of the current study are in agreement with the previous reports in dogs (Axnér & Lagerson ), rams (Ustuner et al . ), and bulls (Crespilho et al .…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…The obtained results clearly demonstrated that egg yolk is superior to soybean lecithin in Tris‐citric‐fructose or Tris‐citric‐fructose‐mineral salts extender when considering motility, plasma membrane integrity, acrosome membrane integrity and mitochondrial membrane potential parameters during 10 days of chilling storage. The results of the current study are in agreement with the previous reports in dogs (Axnér & Lagerson ), rams (Ustuner et al . ), and bulls (Crespilho et al .…”
Section: Discussionsupporting
confidence: 94%
“…Consequently, soybean lecithin is unsuitable for protecting sperm during storage. Thus, centrifuging and filtering are necessary to prepare soybean lecithin extenders as described earlier (de Paz et al 2010;Vick et al 2012;Axn er & Lagerson 2016). However, de Paz et al (2010 have also reported that the centrifugation-filtration process can reduce the quantity of phospholipids in extenders by 50%.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent study in dogs showed that soy lecithin at low concentrations (0.01%, 0.05%, and 0.1%) was not able to maintain sperm characteristics when compared to egg-yolk-based extenders [28]. However, increasing the concentration of soy lecithin to 1% led to promising results on post-thaw semen viability and acrosome integrity in the current study, which is in agreement with previous studies [16,29,30]. This finding supports previous suggestions that high concentrations of soy lecithin are necessary to maintain canine sperm characteristics (i.e., motility kinetics) during storage [28].…”
Section: Discussionsupporting
confidence: 90%
“…One of them is the oxidative stress leading to membrane perturbation and DNA damage. The aim of the extenders is to protect the semen against ice crystal formation, but also to improve the membrane and DNA quality in order to increase the success of fertilization [11,12]. The cryopreservative extender frequently used in veterinary practice could still be optimized to limit the plasma membrane degradation and DNA damage during chilled storage [13,14].…”
Section: Introductionmentioning
confidence: 99%